2003
DOI: 10.1182/blood-2003-01-0108
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis in retinoid-refractory acute myelogenous leukemia by a novel AHPN analog

Abstract: IntroductionAcute myelogenous leukemia (AML) is a heterogeneous disease composed of numerous subclassifications displaying a wide spectrum of phenotypes. 1,2 The major therapeutic approach to this disease has been the use of chemotherapeutic agents with associated life-threatening toxicity. Although nonspecific in their effects, these regimens have significantly increased the survival of AML patients. [3][4][5] Recently, more targeted therapy has been developed. Treatment of acute promyelocytic leukemia (APL) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(54 citation statements)
references
References 70 publications
1
53
0
Order By: Relevance
“…It is likely that other protein factors and/or signal transduction pathways are also involved in the regulation of the Nur77-dependent apoptosis pathway. agreement with previous results (Zhang et al, , 2003Wan et al, 2001;Garattini et al, 2004;BoisvieuxUlrich et al, 2005), and they demonstrate that JNK activation is essential for the apoptotic effects of AHPN and its analogs.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It is likely that other protein factors and/or signal transduction pathways are also involved in the regulation of the Nur77-dependent apoptosis pathway. agreement with previous results (Zhang et al, , 2003Wan et al, 2001;Garattini et al, 2004;BoisvieuxUlrich et al, 2005), and they demonstrate that JNK activation is essential for the apoptotic effects of AHPN and its analogs.…”
Section: Discussionsupporting
confidence: 93%
“…They are known to activate JNK (Zhang et al, , 2003Wan et al, 2001;Garattini et al, 2004;Boisvieux-Ulrich et al, 2005), which is required for maximal apoptosis induction and precedes mitochondrial depolarization. Induction of apoptosis of breast and prostate cancer cells by AHPN is also associated with its inhibition of Akt activity (Farhana et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…3-Cl-AHPC was synthesized as described previously (20,21) and stored at À80jC in DMSO. DMEM-F12 medium, fetal bovine serum, Trizol reagent, and neomycin were purchased from Invitrogen, Inc. (Grand Island, NY).…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that exposure of cells to 3-Cl-AHPC results in the cleavage of Bcl-X L and the generation of a proapoptotic molecule in leukemia cells (20,21). We investigated the effect of 3-Cl-AHPC on c-IAP1, c-IAP2, XIAP, and Bcl-X L in the MDA-MB-468 and DU145 cells.…”
Section: -[3-cl-(1-adamantyl)-4-hydroxyphenyl]-3-chlorocinnamic Acidmentioning
confidence: 99%
See 1 more Smart Citation